2011
DOI: 10.1002/per.822
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Behavior and Personality Traits of the Five Factor Model

Abstract: We examined associations between Five Factor Model personality traits and various outcomes of reproductive behavior in a sample of 15 729 women and men from the Wisconsin Longitudinal Study (WLS) and Midlife Development in the United States (MIDUS) survey. Personality and reproductive history was self-reported in adulthood (mean age: 53 years). High extraversion, high openness to experience, and low neuroticism were associated with larger number of children in both sexes, while high agreeableness and low consc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
168
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 122 publications
(185 citation statements)
references
References 97 publications
14
168
2
1
Order By: Relevance
“…Silka and Kiesler (1977) observed that couples who were intending childlessness or were unsure, expressed greater preference for being alone, were less interested in interaction with people and tended to have more solitary occupations. Extraversion has been positively associated with greater probability of parenthood, earlier parenthood, greater likelihood of non-planned pregnancy, and higher number of children overall (Berg et al 2013;Jokela et al 2011;Tavares 2008;Skirbekk and Blekesaune 2013). The related trait of Sociability (Buss and Plomin 1984) has also been positively associated with the probability of having children (Jokela et al 2009).…”
Section: Extraversionmentioning
confidence: 96%
“…Silka and Kiesler (1977) observed that couples who were intending childlessness or were unsure, expressed greater preference for being alone, were less interested in interaction with people and tended to have more solitary occupations. Extraversion has been positively associated with greater probability of parenthood, earlier parenthood, greater likelihood of non-planned pregnancy, and higher number of children overall (Berg et al 2013;Jokela et al 2011;Tavares 2008;Skirbekk and Blekesaune 2013). The related trait of Sociability (Buss and Plomin 1984) has also been positively associated with the probability of having children (Jokela et al 2009).…”
Section: Extraversionmentioning
confidence: 96%
“…Openness to experience (intellect; creativity) was negatively related to fertility in British women, partly because it positively predicted educational uptake and fertility postponement [94]. This has been echoed in males [94] and increasingly in younger birth cohorts for both sexes [95], though inconsistently [96]. Agreeableness (cooperativeness; empathy) predicts higher fertility at least in females [95], also including reproductive acceleration [94].…”
Section: (D) Personalitymentioning
confidence: 99%
“…For example, in a large U.S. sample, higher extraversion was associated with earlier transition to parenthood and with having a larger number of children (Jokela, Alvergne, Pollet, & Lummaa, 2011). High openness to experience and high neuroticism had the opposite effect.…”
mentioning
confidence: 98%